2011
DOI: 10.1111/j.1744-6198.2011.00224.x
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Utilization Among Patients With Vocal Cord Dysfunction

Abstract: Nurse practitioners and other healthcare providers are challenged to reduce unnecessary inhaler prescribing among patients with VCD without asthma and to seek specialty consultation to confirm or refute the diagnosis of asthma when needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 7 publications
0
8
0
3
Order By: Relevance
“…Untreated BVFP can lead to a loss of voice, reduced professional prospects, and a lower social status. Living with permanent dyspnea, however, limits physical activity both in professional and everyday life and is a detrimental factor for overall health and well‐being . Studies have reported contradictory results after glottal enlargement surgery and have not given detailed descriptions of the patients’ symptoms and complaints .…”
Section: Introductionmentioning
confidence: 99%
“…Untreated BVFP can lead to a loss of voice, reduced professional prospects, and a lower social status. Living with permanent dyspnea, however, limits physical activity both in professional and everyday life and is a detrimental factor for overall health and well‐being . Studies have reported contradictory results after glottal enlargement surgery and have not given detailed descriptions of the patients’ symptoms and complaints .…”
Section: Introductionmentioning
confidence: 99%
“…Эндоскопическое исследование с прямой визуализацией вокальных складок с помощью гибкой трансназальной волоконно-оптической ларингоскопии во время обострения является «золотым стандартом» в диагностике вокальной дисфункции связок [4,7,24]. Наличие стимуляции вдоха является ключом к постановке диагноза [25].…”
Section: диагностика и дифференциальная диагностикаunclassified
“…Во время обострения заболевания жалобы пациента с вокальной дисфункцией не соответствуют объективным результатам [25]. Дифференциально диагностическое значение имеет соотношение фазы вдоха и выдоха.…”
Section: диагностика и дифференциальная диагностикаunclassified
See 1 more Smart Citation
“…PVFMD is likely underdiagnosed and this has been shown to lead to increased health care costs [50][51][52]. The prevalence is unknown as there are no large, prospective, population based studies [53].…”
Section: Epidemiologymentioning
confidence: 99%